Kinetic Evidence for Near Irreversible Nonionic Micellar Entrapment of N-(2′-Methoxyphenyl)phthalimide (1) under the Typical Alkaline Reaction Conditions - M. Niyaz Khan; Yoke-Leng Sim; Azhar Ariffin (The Scientific World Journal)
The values of pseudo-first-order rate constants (kobs) for alkaline hydrolysis of 1, obtained at 1.0 mM NaOH and within CmEnT (total concentration of CmEn) range of 3.0–5.0 mM for C12E23 and 10–20 mM for C18E20, fail to obey pseudophase micellar (PM) model. The values of the fraction of near irreversible CmEn micellar trapped 1 molecules (FIT1) vary in the range ~0–0.75 for C12E23 and ~0–0.83 for C18E20 under such conditions. The values of FIT1 become 1.0 at ≥10 mM C12E23 and 50 mM C18E20. Kinetic analysis of the observed data at ≥10 mM C12E23 shows near irreversible micellar entrapment of 1 molecules under such conditions.